2014
DOI: 10.1371/journal.pone.0087685
|View full text |Cite|
|
Sign up to set email alerts
|

Milrinone Relaxes Pulmonary Veins in Guinea Pigs and Humans

Abstract: IntroductionThe phosphodiesterase-III inhibitor milrinone improves ventricular contractility, relaxes pulmonary arteries and reduces right ventricular afterload. Thus, it is used to treat heart failure and pulmonary hypertension (PH). However, its action on pulmonary veins (PVs) is not defined, although particularly PH due to left heart disease primarily affects the pulmonary venous bed. We examined milrinone-induced relaxation in PVs from guinea pigs (GPs) and humans.Material and MethodsPrecision-cut lung sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
0
22
1
Order By: Relevance
“…PCLS from BALB/c mice and human PCLS were prepared as described 36 , 43 . Briefly, mice were anaesthetised intraperitoneally (160 mg/kg pentobarbital) and the depth of anaesthesia was monitored by missing reflexes.…”
Section: Methodsmentioning
confidence: 99%
“…PCLS from BALB/c mice and human PCLS were prepared as described 36 , 43 . Briefly, mice were anaesthetised intraperitoneally (160 mg/kg pentobarbital) and the depth of anaesthesia was monitored by missing reflexes.…”
Section: Methodsmentioning
confidence: 99%
“…In man, the PDE3 and PDE5 inhibitors, milrinone and sildenafil, have previously been shown to decrease systemic arterial BP by 5–10 mmHg (Ludmer et al , ; Vardi et al , ) and to induce vasodilatation in pulmonary and systemic arteries from rat and man (Andersen et al , ; Grzesk et al , ; Rieg et al , ). In agreement with these findings, we found that sildenafil and milrinone relaxed rat mesenteric and femoral arteries.…”
Section: Discusssionmentioning
confidence: 99%
“…These improvements have led to the wide application of the PCLS technique [7, 9–11]. Ever since, PCLS from different species have been used for the assessment of pharmacological and toxicological compounds [7, 9, 10], as well as to model airway constriction [6].…”
Section: Introductionmentioning
confidence: 99%